Effect Of pH And Contact Time On The Adsorption Of Heavy Metals In Acid Mine Drainage Using Hydrated Lime - Chamnek, Arvitcha (Universiti Sains Malaysia, 2018)
Acid mine drainage (AMD) is one of the most problematic occurrence that can cause environmental degradation to the ecosystems, human health, and may devastate the water security in the area. The major problem with AMD is the content of heavy metals in it and if neglected may pose a major threat to the human health. Since today, many research was done to treating the acid mine drainage but less is known on how the pH and contact time of adsorbent material affects the heavy metals concentration. This study present the results of a study conducted in Pengkalan Hulu, Perak where real acid mine drainage water sample is taken to be treated. This study also aims to analyze the characteristic of AMD water sample and composition of adsorbent media as well as to observe the optimum pH and contact time for treatment of acid mine drainage sample using hydrated lime as the adsorbent material. The study shows that longer contact time is needed for the highest percentage of adsorption of heavy metals. However, pH varies for each of the heavy metals to be adsorbed at maximum. This project is significant to comply with the standard set in Mineral Development (Effluent) Regulations 2016 to sustain the environmental quality.